European Resuscitation Council and European Society of Intensive Care Medicine Guidelines 2021: Post-resuscitation care. (April 2021) - Nolan, Jerry P.; Sandroni, Claudio; Böttiger, Bernd W.; Cariou, Alain; Cronberg, Tobias; Friberg, Hans; Genbrugge, Cornelia; Haywood, Kirstie; Lilja, Gisela; Moulaert, Véronique R.M.; Nikolaou, Nikolaos; Mariero Olasveengen, Theresa; et al.
Abstract: The European Resuscitation Council (ERC) and the European Society of Intensive Care Medicine (ESICM) have collaborated to produce these post-resuscitation care guidelines for adults, which are based on the 2020 International Consensus on Cardiopulmonary Resuscitation Science with Treatment Recommendations. The topics covered include the post-cardiac arrest syndrome, diagnosis of cause of cardiac arrest, control of oxygenation and ventilation, coronary reperfusion, haemodynamic monitoring and management, control of seizures, temperature control, general intensive care management, prognostication, long-term outcome, rehabilitation, and organ donation.